Kontribusi Panti Asuhan terhadap Pemenuhan Hak Pendidikan dan Pengembangan Potensi Anak Yatim Piatu - Alif Diki Setiawan; Abdullah Rafif; Rahmat Abrar Hasayang Hrp; Rabvalco Giotara; Albie Ilhami; Waldi Gustio Anugrah Mulya; Muhammad Rasyid Halim Srg; Akbar Mirza Efendi; M. Gilang Rayarafhaeld; Azril Burhan Kurniadi; T Pandu Saputra; Muhammad Arya Sabbait; Ere Mardella Arbiani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Education is a basic right for every child, including orphans. Orphanages play a crucial role in fulfilling the right to formal education and developing the potential of orphans, particularly in areas with limited resources. This study analyzes the contribution of orphanages in providing inclusive education and practical skills through vocational programs. The method used is a literature review with content analysis to identify the role of orphanages in education and character development. The results show that orphanages not only provide formal education but also develop character through informal education and life skills. However, orphanages face challenges related to limited resources and dependence on donations. Therefore, collaboration with the government, educational institutions, and the community is needed to overcome these challenges and ensure optimal education.